PENTINGNYA PENDIDIKAN BAGI ANAK JALANAN - Fetriani, Fetriani; Zulyan, Zulyan; Hasibuan, Muslih; Saputra, Eki; Qurniati, Amnah (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Everyone should get an education, whether rich or poor people. Education is one of the efforts that must be prepared to welcome a better future. The better the education we get, the better the lifestyle we feel. Unfortunately, there are still many Indonesian children who do not get an education. Poverty, lack of parental responsibility and laziness are factors that cause a child to not get an education. Not getting an education decided them to go down and make a living on the street. These children are what we usually called as street children. In this regard, it is important to conduct coaching activities for these children through counseling, by explaining the importance of education for street children